Deflation and middle-class in Indonesia: An empirical analysis in January 2022-January 2025 - Marro'aini, Marro'aini (International Journal of Applied Finance and Business Studies, 2025)
This study examines the relationship between deflationary trends and the contraction of the middle class in Indonesia between January 2022 to January 2025. Utilizing macroeconomic data from Bank Indonesia and the Central Statistics Agency (BPS), the research analyzes key indicators such as inflation rates, consumer price index (CPI), household consumption, and asset value fluctuations. The findings reveal that while deflation eased cost pressures in some sectors, it also led to declining business revenues, wage stagnation, and job insecurity, particularly affecting middle-income workers in retail, manufacturing, and services. The increased real burden of household debt and declining asset values further undermined middle-class financial stability. During this period, the proportion of middle-class citizens dropped to 17.13% of the population, accompanied by shrinking savings, reduced consumption, and changing spending behavior; such as a decline in car purchases and a rise in motorcycle sales. The research highlights the dual nature of deflation as both a short-term relief and a long-term economic risk, emphasizing the need for targeted policies to safeguard middle-class resilience and maintain sustainable economic growth in Indonesia.